Celebrity Culture and Journalism Practice in Nigeria - Ololade Olatunji Lateef (Konfrontasi: Jurnal Kultural, Ekonomi dan Perubahan Sosial, 2024)
Celebrity culture and journalism practice in Nigeria are closely intertwined, reflecting the growing influence of celebrities in shaping public opinion, culture, and media consumption. Nigerian celebrities are often products of the media, with platforms like social media, television, and magazines playing a central role in constructing their public identities. The media industry works to build and maintain celebrity brands, which in turn influences public perception and the celebrity's influence on society. The paper argues that celebrities in Nigeria have a strong presence on social media platforms like Instagram, Twitter, and TikTok, which amplify their voices and increase their visibility. This has changed the traditional way celebrities are covered by the media, with social media now serving as an important news source and space for celebrities to control their narratives. In Nigeria, entertainment journalism is a significant aspect of mainstream media. A considerable portion of news, especially in tabloids and online media outlets, focuses on celebrity gossip, lifestyle, and controversies. The rise of entertainment reporting has shifted some media outlets from hard news to a more sensational and celebrity-focused approach. The paper concludes that celebrity culture in Nigeria is a major influence on journalism, with entertainment and celebrity news playing a pivotal role in the media landscape. However, this trend comes with ethical challenges, such as maintaining accuracy, respecting privacy, and balancing sensationalism with responsible reporting.